Relationship Between CBR Value and Soil Compaction Under Various Number of Blows - Nadra Mutiara Sari; Darma Hendra; Soegeng Haridjadi; Ajun Wiratama; Rifki Adisyaputra (Universitas Negeri Padang, 2025)
Subgrade is one of the essential components in road pavement construction, particularly in flexible pavement. This is because the subgrade serves as the foundation that supports the overall load above it. Therefore, it must have a high bearing capacity with a minimum California Bearing Ratio (CBR) value of 6%. To achieve this requirement, efforts to increase the CBR value are needed, one of which is through soil embankment and compaction. In this study, soil compaction was carried out to obtain the desired CBR value. The sample consists of 18 samples with each impact variation (25, 35, 45, 55, 65, and 75 times) being three samples. The fill soil comes from the Gandus area, Palembang city. The test results showed the lowest CBR value of 2.79% at 25 blows with a dry density of 1.51 g/cm³, and the highest value of 14.23% at 75 blows with a dry density of 1.95 g/cm³. At 45 blows, a CBR value of 8.05% with a dry density of 1.78 g/cm³ was obtained, which already meets the subgrade requirement. It can thus be concluded that the greater the number of blows, the higher the CBR value. However, the dry density did not significantly increase beyond 55 blows, indicating that the soil had reached a sufficient level of compaction with minimal air voids, and further compaction was unnecessary since the standard CBR value had been achieved.